Discovery of Racism in the Fantasy Genre. The Dark Elf Motif in Dungeons & Dragons - Strzelczyk, Agata (Journal of Gender and Power, 2022)
The fantasy genre bares some stigmas born from the times of its most formative author, J.R.R. Tolkien. Among them, there is a problem of so-called “fantasy races”, imaginary entities like elves, orcs, or goblins, and their real-world implications, rooted deeply in racial stereotypes. In this article, I study this topic on the example of the fictional race of the drow or dark elves and their portraits in the media related to Dungeons & Dragons, a tabletop roleplay game system heavily influenced by classic fantasy motifs. I try to argue that the changes in social and racial sensitivity observed in the young generation of Dungeons & Dragons players are correlated with changes in the portrayal of draws from classic monsters to much more nuanced approaches.